Community resistance as an experience of peacebuilding and social dialogue in the Cañón de las Hermosas (Colombia) - Presta Novello, Déborah; Tafur Villarreal, Andrés (REVISTA ELECTRONICA IBEROAMERICANA, 2022)
The Cañón de las Hermosas is located in the center of Colombia, on one of the ramifications of the Andes Mountain Range. Several of the most recurrent symptoms in the diagnosis of the armed conflict in Colombia were concentrated there: poverty, inequality, precariousness and institutional weakness, social and territorial control of armed groups, disputes over illegal income derived from the cultivation and trafficking of illicit drugs, and impacts on territoriality and territory. In a completely adverse climate, the community itself has been able to launch various civil resistance mechanisms for the protection of the population that have been recognized as a effective platforms aimed at social dialogue and the construction of peace.